Finite-Element Model for Laminated Beam-Plates Composite Using Layervise Displacement Theory - Rosca, V.E.; Poteraşu, V.F.; Ţăranu, N.; Rosca, B.G (Engineering Transactions, 2002)
The paper uses the layerwise theory, i.e. the zigzag behaviour of the in-plane displacements through the thickness, and the Lagrange interpolation functions for finite element to compute the stresses and displacements in beams made by composite materials. The layerwise method can determine the interlaminar stresses and other localized effects with the same accuracy as 2D finite element method but less computer effort. We present as illustration two examples.